2011
DOI: 10.5336/medsci.2010-19299
|View full text |Cite
|
Sign up to set email alerts
|

Can Postoperative Pain and Analgesic Need be Predicted in Preoperative Period?

Abstract: Ö ÖZ ZE ET T A Am ma aç ç: : Bu ça lış may la has ta nın pre o pe ra tif ba sınç ağ rı eşi ği, ank si ye te ve kor ti zol dü zey le ri ve de mog ra fik ve ri leri ile pos to pe ra tif ağ rı dü ze yi ve anal je zik ih ti ya cı ara sın da ki iliş ki yi de ğer lendir me yi amaç la dık. G Ge e r re eç ç v ve e Y Yö ön n t te em m l le er r: : Etik ku rul ona yı ve has ta la rın ya zı lı iz ni alın dık tan son ra la pa ros ko pik ko le sis tek to mi uy gu la na cak ASA I-II 40 has ta ça lış ma ya alın dı. Pre o pe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
3
5
1
1
Order By: Relevance
“…Similar results were obtained by Turner et al, in which female patients who had spinal cord damage tended to catastrophize significantly more than male patients (19). In a recent study, Kırdemir and Özorak put forth that women perceived pain more intensely due to the fact that their threshold to pressure pain was lower than men's (20). In a study of 36 male and 64 female patients with knee osteoarthritis, Keefe et al also suggested that female patients' PCS scores were higher than those of males (16).…”
Section: Discussionsupporting
confidence: 74%
“…Similar results were obtained by Turner et al, in which female patients who had spinal cord damage tended to catastrophize significantly more than male patients (19). In a recent study, Kırdemir and Özorak put forth that women perceived pain more intensely due to the fact that their threshold to pressure pain was lower than men's (20). In a study of 36 male and 64 female patients with knee osteoarthritis, Keefe et al also suggested that female patients' PCS scores were higher than those of males (16).…”
Section: Discussionsupporting
confidence: 74%
“…In the literature, it has been stated that gender has an association with pain, and women complain about pain more frequently than men and use analgesic drugs more regularly (Önder, Koçıa et al 2002 , Kırdemir andÖzorak 2011). In the present study, women in the control group had higher VPS (pain) values prior to the procedure, and this result is similar with those in the literature.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study; the age, educational status and the presence of a chronic disease, which are included in the sociodemographic characteristics, were not found to significantly affect the perception of pain (Kırdemir and Özorak 2011). Reported that there is no correlation between age and pressure pain threshold (Kırdemir and Özorak 2011).…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Another study used a psychological test (State-Trait Anxiety Inventory – STAI) to measure preoperative state and trait anxiety of the patients and demonstrated that preoperative STAI scores correlated with postoperative analgesic consumption [28]. Kırdemir and Özorak [29] suggested that the dose of required postoperative analgesics should be planned preoperatively based on the physical and psychological state of the patients. Our findings also suggest that the postoperative analgesic requirements may vary among patients and that their requirements might be predicted using preoperative indicators; serum leptin levels could be one such indicator, and the patient’s postoperative analgesic regimen might be planned accordingly.…”
Section: Discussionmentioning
confidence: 99%